The genetic basis of Parkinson's disease - A. A. Tappakhov (Nevrologiâ, Nejropsihiatriâ, Psihosomatika, 2017)
Parkinson's disease (PD) is a multifactorial disease that develops in the presence of both genetic and environmental factors. In recent years, there has been sufficient information on the role of genetic predisposition in the development of not only familial cases, but also sporadic ones. A hereditary burden in PD may not be traced in cases of recessive inheritance with a low gene penetrance, as well as in a patient's death before the onset of the disease. Active introduction of molecular genetic methods, including next generation sequencing, can annually identify new gene mutations that underlie sporadic PD cases. This paper provides an overview of the current literature on the genetic aspects of PD with emphasis on the ethnic characteristics of the disease.